1995
DOI: 10.1107/s0907444995005415
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray crystallographic data withEscherichia colitransketolase

Abstract: The Escherichia coli enzyme transketolase, a dimeric protein of 2 x 70 kDa (662 amino acids) has been prepared from an overexpression system in E. coli. The purified enzyme has been crystallized from PIPES buffer pH 6.4 and ammonium sulfate. The crystals which grow as large plates diffract to greater than 1.9 A, resolution and are of the space group P2(1)2(1)2(1) with unit-cell dimensions of a = 74.6, b = 125.6 and c = 151.0 A, (Z = 8 with one transketolase dimer in the asymmetric unit). The structure has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 2 publications
3
39
0
2
Order By: Relevance
“…The three-dimensional structure of the latter enzyme [93,111] has been published (PDB accession code 1TRK) and crystallographic studies on the E. coli enzyme have commenced [94]. Homologous expression systems are established for the S. cerevisiae [155] and the E. coli [60,153] enzyme.…”
Section: Sources Of Tkmentioning
confidence: 99%
“…The three-dimensional structure of the latter enzyme [93,111] has been published (PDB accession code 1TRK) and crystallographic studies on the E. coli enzyme have commenced [94]. Homologous expression systems are established for the S. cerevisiae [155] and the E. coli [60,153] enzyme.…”
Section: Sources Of Tkmentioning
confidence: 99%
“…The 3D protein crystal structures of the microbial TKs from Escherichia coli (Littlechild et al, 1995), Saccharomyces cerevisiae (Sundstrom et al, 1993), Bacillus anthracis (Maltseva et al, 2009) and human TK (Mitschke et al, 2010) have been resolved and show high structural homologies. All these TKs are homodimers with two active sites located at the interface between the contacting monomers.…”
Section: Introductionmentioning
confidence: 98%
“…A comparison between these three homologous enzymes has revealed that physicochemical properties such as the pH optimum or the stability of the activity are very similar. Previously, the three-dimensional structure of S. cerevisiae TK has been resolved to 2.0 A Ê [18] and preliminary crystallographic data on the E. coli enzyme have been published [16]. This structural information allowed the identi®cation of residues predicted to be involved in various parts of the enzyme's function, e.g.…”
Section: Introductionmentioning
confidence: 99%